(f o g)(x)
g(x) = x + 2
Since it’s telling you to use g(x), you use (x + 2) as your new x value for function f.
f(x + 2) = 5(x + 2) + 5
= 5x + 10 + 5
= 5x + 15
A. 40x^2 + 240x + 200
Shape: Rectangle
Formula: A = LW
A = (10x + 10)(4x + 20)
= (10x)(4x) + (10x)(20) + (10)(4x) + (10)(20)
= 40x^2 + 200x + 40x + 200
= 40x^2 + 240x + 200
————————————————————-
2. 57,600 ft^2
Width:
4x + 20 = 160
4x = 140
x = 35
Plug-In:
10x + 10
10(35) + 10
350 + 10
360 = Length
————————————-
A = LW
A = 360 • 160
A = 57,600 ft^2
Answer:
Step-by-step explanation:
(x₁, y₁) = (-9 ,8) and (x₂ , y₂) = (-3 , -1)
![Slope = \dfrac{y_{2}-y_{1}}{x_{2}-x_{1}}\\\\=\dfrac{-1-8}{-3-[-9]}\\\\=\dfrac{-9}{-3+9}\\\\=\dfrac{-9}{6}\\\\=\dfrac{-3}{2}](https://tex.z-dn.net/?f=Slope%20%3D%20%5Cdfrac%7By_%7B2%7D-y_%7B1%7D%7D%7Bx_%7B2%7D-x_%7B1%7D%7D%5C%5C%5C%5C%3D%5Cdfrac%7B-1-8%7D%7B-3-%5B-9%5D%7D%5C%5C%5C%5C%3D%5Cdfrac%7B-9%7D%7B-3%2B9%7D%5C%5C%5C%5C%3D%5Cdfrac%7B-9%7D%7B6%7D%5C%5C%5C%5C%3D%5Cdfrac%7B-3%7D%7B2%7D)
Answer:
k=3
Step-by-step explanation:
+ we note f(p)= ![p^{4}+p^{2} +p -k](https://tex.z-dn.net/?f=p%5E%7B4%7D%2Bp%5E%7B2%7D%20%20%2Bp%20-k)
+ Because of "p-1 is a factor of f(p)", that means f(p)= (p-1)* g(p)
Then we have f(1)= (1-1)*g(1)= 0* g(1)= 0
+ We replace p=1 in f(p) and we have:
f(1)=0
that means: ![1^{4}+1^{2} + 1 - k=0](https://tex.z-dn.net/?f=1%5E%7B4%7D%2B1%5E%7B2%7D%20%2B%201%20-%20k%3D0)
then 1+1+1-k = 0, 3-k=0 or k=3
Hope that useful for you.